Barthélémy Toguo - faith can move mountains Villa Merkel, Galerie der Stadt Esslingen - Baur, Andreas 1958- (Snoeck, 2023)
Barthélémy Toguo (*1967) has been focusing in his artistic practice on highly topical issues of identity and social belonging, like migration, flight, displacement, and the restrictions that stem from territorial borders and politics regarding sovereign rights. Against the background of his dual Cameroonian-French citizenship, he thereby explicitly adopts an anti-Eurocentric approach. He is above all concerned about the causes of ecological problems and their impact on society: drinking and industrial water shortages, maldevelopments in agriculture, the effects of climate change, corruption, armed conflicts, lack of economic development prospects, and much more. In his works – ranging from painting, drawing, sculpture, and performance to installation – he connects human concerns with nature: »What guides me is a constantly evolving aesthetic, but also a sense of ethics, which makes a difference and structures my entire approach.« Published in this book are works created especially for the Esslingen exhibition, as well as remakes and adapted installations; also included is a small retrospective overview of the artist’s work
Impressum: Diese Publikation erscheint anlässlich der Ausstellung "Barthélémy Toguo - Faith Can Move Mountains", Villa Merkel, Galerie der Stadt Esslingen, 7.8. - 23.10.2022
Keywords: Toguo, Barthélémy -- 1967-; Ausstellungskatalog -- Villa Merkel, Galerien der Stadt Esslingen am Neckar -- 07.08.2022-23.10.2022 -- Esslingen am Neckar